Venetian vespers - Banville, John (Alfred A. Knopf, 2025)
Everything was a puzzle, everything a trap set to mystify and hinder me. 1899. As the new century approaches, English hack-writer Evelyn Dolman marries Laura Rensselaer, the daughter of a wealthy American plutocrat. But in the midst of a mysterious rift between Laura and her father, Evelyn's plans of a substantial inheritance are thrown into doubt. As the unhappy newlyweds travel to Venice at Palazzo Dioscuri - the ancestral home of the charming but treacherous Count Barbarigo - a series of seemingly otherworldly occurrences exacerbate Evelyn's already frayed nerves: is it just the sea mist blanketing the floating city or is he losing his mind?